(untitled) (Portuguese Journal of Family Medicine and General Practice, 2024)
The reform of primary healthcare (PHC) in Portugal, initiated in 2007 with the creation of Family Health Units (FHU) and Health Center Groups (ACeS), marked a significant turning point in restructuring the National Health Service (NHS). However, implementing Local Health Units (LHU) in 2024 poses challenges and uncertainties that require a well-founded, evidence-based approach. An analysis of healthcare professionals’ expectations revealed concerns such as the limited autonomy of FHUs and the unequal distribution of investments between primary and secondary care, emphasizing the need for transparent, participatory dialogue in NHS reforms. The exclusion of healthcare professionals from LHU-related decision-making and the absence of bottom-up planning undermines the acceptance and efficacy of the model. Furthermore, threats to the clinical leadership of PHC, including legislation on the appointment of clinical directors and loss of autonomy, are critical issues that necessitate proactive measures to preserve the integrity and effectiveness of these units. Organizational challenges, such as the replication of hospital-centric management models that fail to address the specificities of PHC and a diminished leadership role in executing the Recovery and Resilience Plan, further jeopardize the organizational culture and performance of PHC. To secure the effectiveness and quality of PHC within LHU, it is crucial to implement strategies that engage professionals, bolster clinical leadership, and protect the autonomy of family health teams. The establishment of ACeS, I.P., offers a viable alternative by granting administrative independence and enhancing efficiency in PHC delivery. All these efforts must be driven by a unified commitment and collaborative strategy aimed at the ongoing improvement of the NHS and the well-being of the Portuguese population.